The impact of fiscal shocks on the Irish economy - Benetrix, Agustin S.; Lane, Philip R. (Economic & Social Studies, 2009)
We study the short-run effects of shocks to government spending on Ireland?s output and its real exchange rate. We show that the impact of government spending shocks critically depend on the nature of the fiscal innovation. Our main finding is that there are important differences between shocks to public investment and shocks to government consumption. Moreover, within the latter category, shocks to the wage and non-wage components also have dissimilar effects.
Keywords: Fiscal policy; Ireland; Shocks; Exchange rate